Analisis Penerapan Risk Management Sebagai Upaya Efektivitas Pengumpulan Dana Zakat Pada BAZNAS Provinsi SumateraUtara - Safarilla, Eka; Pradesyah, Riyan (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the application of risk management and find out the obstacles that occur in the National Amil Zakat Board of North Sumatra Province. The research approach used is a qualitative research method with a descriptive approach. Data collection techniques used in this study are observation, interviews, documentation and literature study. The data validation technique uses the triangulation method. Respondents in this study consisted of deputy chairmen of one field of zakat fund collection and amil implementing unit four of the Human Resources and General Administration Section. The results of the study show that the implementation of risk management in the National Amil Zakat Agency for North Sumatra Province has been implemented, it's just that in implementing risk management there are several obstacles, such as the lack of human resources who understand IT, and there is no evaluation of risk management. While the risk management process is carried out by identifying risks, then monitoring risks and controlling risks. The obstacles that occurred at the National Amil Zakat Agency for North Sumatra Province in collecting zakat funds at the National Amil Zakat Agency for North Sumatra Province were in the form of a lack of coordination, facilities and infrastructure in collecting zakat funds.